Labelling Kemasan Sebagai Upaya Pengembangan Pemasaran Agroindustri Emping Jagung di Desa Tirtomulyo, Kretek, Bantul - Farid Setyawan; Pinjung Nawang Sari (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2016)
Tirtomulyo Village is located in the sub-district of Kretek, at the southern tip of Bantul District. Agricultural potential in this village is still widely open including their processed products, considering the productive lands are suitable for any kind of crops, i.e. corn. Corn is one of the most planted crops in this village. For extra earning, corns are also used as raw materials in processed corn products, i.e. corn chips. Corn chips industry in this village is quite well developed but the lack of packaging and labelling make this agroindustry a little hampered in its marketing. The method used in this research is to mentoring and educating the coummunity especially the agroindustry persons about the marketing strategy, particularly the packaging and labelling. Results from this service, the community succeed to make branding, labelling, and registration in the Department of Health and the Department of Industry, Trade and Cooperatives at Bantul District as a household industry based on processed agricultural products. By labelling the products and has been registered at the relevant institutions, it is expected that the corn chips agroindustry is being stimulated and developed in a much broader scale.